Effects of Lactobacillus hilgardii 60TS-2, with or without homofermentative Lactobacillus plantarum B90, on the aerobic stability, fermentation quality and microbial community dynamics in sugarcane top silage. (September 2020) - Wang, Tianwei; Teng, Kunling; Cao, Yanhong; Shi, Weixiong; Xuan, Zeyi; Zhou, Jianhui; Zhang, Jie; Zhong, Jin
Highlights: Sugarcane tops ensiled with LH and homofermentative LP were analyzed. LH and LHLP addition improved the aerobic stability of sugarcane tops silage. LH and LHLP stabled pH value and organic acid contents after aerobic exposure. Combined addition of LH and LP showed least DM loss after 5 days of aerobic exposure. L. hilgardii inhibited spoilage microorganisms: A. pasteurianus and K. humilis. Abstract: This study investigated the effects of Lactobacillus hilgardii (LH), alone or in combination with Lactobacillus plantarum (LP), on the aerobic stability, fermentation quality and dynamics of the bacterial and fungal communities of sugarcane top silage. Results demonstrated that LH and LHLP (LH combined with LP) improved the aerobic stability of sugarcane top silages. As the exposure time increased, the pH values and the contents of lactic acid, acetic acid, as well as propionic acid remained stable in silage treated with LH and LHLP. The abundance of L. hilgardii was enriched and the undesirable microorganisms, such as Acetobacter pasteurianus, Paenibacillus amylolyticus and yeasts like Kazachstania humilis, were suppressed in silages treated with LH and LHLP. In conclusion, LH-treated silage, whether with LP or not, positively impacted the fungal and bacterial microbes. This improved the quality of fermentation, the aerobic stability, and reduced aerobic spoilage in sugarcane top silage.